Preoperative patient preparation in enhanced recovery pathways - Usama Iqbal; Jeremy B Green; Srikant Patel; Yiru Tong; Marcus Zebrower; Alan D Kaye; Richard D Urman; Matthew R Eng; Elyse M Cornett; Henry Liu (Wolters Kluwer Medknow Publications, 2019)
Enhanced recovery pathways are a novel approach focused on enhancing the care of surgical patients. "Prehabilitation" is the term applied to any intervention administered before surgery to reduce surgery-related morbidity, decrease the length of hospital stay, expedite the return of organ function, and facilitate the patient's return to normal life. A PubMed search was performed with the following key words: enhanced recovery, preoperative preparation, cessation of smoking and euvolemia. The results from this Pubmed search revealed that female patients may have higher levels of anxiety than male patients. Intensive smoking and alcohol cessation 6-8 weeks before elective surgery may reduce the incidence of postoperative morbidity. Preoperative exercise can be effective for reducing the postoperative complications like pulmonary complications and shortening the length of hospital stay. It is safe to allow patients to drink clear fluids up until 2 h before elective surgery (Level II evidence). Perioperative normoglycemia is the single most important factor to prevent surgical site infection. Intermittent pneumatic compression devices and low molecular weight heparin are effective in preventing postoperative thromboembolism. No advantage is gained by preoperative mechanical bowel preparation in elective colorectal surgery. The goal of preoperative fluid management is for the patient to arrive in the operating room in a hydrated and euvolemic state. Mild perioperative hypothermia may promote surgical wound infection by triggering thermoregulatory vasoconstriction, which decreases subcutaneous oxygen tension.